Votive Offerings, Graffiti, or Scribal Exercises? A Note on the grmlqr[t] Inscription from Sarepta and the “Blessings” from Kuntillet ʿAjrud - Wearne, Gareth J. (2023)
This short article revisits the question whether a class of inscriptions from the Phoenician city of Sarepta and the Israelite settlement at Kuntillet ʿAjrud should be understood as votive offerings, graffiti, or scribal exercises. It argues that differences in the manner of execution mean the Sarepta and Kuntillet ʿAjrud inscriptions resist attempts to impose a single unifying explanation. By doing so, it yields insights into the nature of sacrificial terminology in the world of the Hebrew Bible and offers a more nuanced understanding of the mlkʾmr sacrifices that are named in some Punic inscriptions.